Obtención de bebida hidratante a partir de acai Euterpe oleracea camu camu Myrciaria dubia y agua de coco cocos nucifera - Vela Rodríguez, Ana Yolanda (2023)
This research was developed at the C.I.R.N. A (Centro de Investigación Recursos Naturales), being the objective to find an ideal formulation with the three components that were Acai, camu camu pulp and coconut water, where three formulations based on these raw materials were proposed, following the method of mixing and finding the perfect dilution for this type of hydrating drink product, first evaluating the physical-chemical, microbiological and sensory tests such as: odor, color, brix degrees, flavor, and acidity, subsequently a process flow was raised from each raw material, independently, being the exact dilution of these three raw materials (1:dehydrated acai, 1:camu camu pulp and 6: coconut water), resulting in the following contents of total solids 6. 37%, soluble solids 5.60oBrix, pH(20o C) 4.23, titratable acidity (expressed in citric acid) 0.35% and vitamin C 100. 20 mg/100 g, consequently the microbiological results reported the content of fungi